Preexisting Immunity, More Than Aging, Influences Influenza Vaccine Responses. (15th April 2015) - Reber, Adrian J.; Kim, Jin Hyang; Biber, Renata; Talbot, H. Keipp; Coleman, Laura A.; Chirkova, Tatiana; Gross, F. Liaini; Steward-Clark, Evelene; Cao, Weiping; Jefferson, Stacie; Veguilla, Vic; Gillis, Eric; et al.
Abstract: Background.  Influenza disproportionately impacts older adults while current vaccines have reduced effectiveness in the older population. Methods.  We conducted a comprehensive evaluation of cellular and humoral immune responses of adults aged 50 years and older to the 2008–2009 seasonal trivalent inactivated influenza vaccine and assessed factors influencing vaccine response. Results.  Vaccination increased hemagglutination inhibition and neutralizing antibody; however, 66.3% of subjects did not reach hemagglutination inhibition titers ≥ 40 for H1N1, compared with 22.5% for H3N2. Increasing age had a minor negative impact on antibody responses, whereas prevaccination titers were the best predictors of postvaccination antibody levels. Preexisting memory B cells declined with age, especially for H3N2. However, older adults still demonstrated a significant increase in antigen-specific IgG + and IgA + memory B cells postvaccination. Despite reduced frequency of preexisting memory B cells associated with advanced age, fold-rise in memory B cell frequency in subjects 60+ was comparable to subjects age 50–59. Conclusions.  Older adults mounted statistically significant humoral and cell-mediated immune responses, but many failed to reach hemagglutination inhibition titers ≥40, especially for H1N1. Although age had a modest negative effect on vaccine responses, prevaccination titers were the best predictor of postvaccination antibody levels, irrespective of age.